Assessment of school zoonotic diseases awareness program among primary school students of Sekolah Kebangsaan Seri Selangor USJ4, Subang Jaya Selangor - Shafie, Hazlini (2017)
Humans are prone to be infected with zoonotic diseases from wildlife/domestic animals and the environment. It is important for public especially school students to be aware of zoonotic diseases in order to prevent zoonotic disease transmission when handling animals. Thus, this study was carried out to determine the awareness on zoonotic diseases among primary school students of Sekolah Kebangsaan Seri Selangor USJ4, Subang Jaya, Selangor before and after the school zoonotic diseases awareness program and as well as to assess the effectiveness of the program in educating students on zoonotic diseases . The awareness program conducted consists of eight modules and each module comprises of a few activities related zoonotic diseases education for school students. The program was divided into two phases, first phase was conducted on the 5th October 2016 at the school followed by the second phase on the 10th October 2016 in UPM. A set of questionnaire on zoonotic diseases was designed to assess the awareness and knowledge of students on zoonotic diseases. The questionnaires (pre-survey forms) were distributed among the students to be answered before the students were introduced to the zoonotic diseases topics in the awareness program and the questionnaires (post-survey forms) which consist of the same questions as in pre-survey forms were distributed again after the the school zoonotic diseases awareness program and activities finished. A total of 40 respondents were obtained. Mann Whitney U-Test was used to analyze the data by each question. Significant difference (P<0.05) in awareness on zoonotic diseases by each question was observed among primary school students of Sekolah Kebangsaan Seri Selangor, USJ4 between before and after the awareness program. (89.1%) from 35 total of questions had significant difference (P<0.05) in awareness on zoonotic diseases between before and after the program was conducted. Thus, we can conclude that the program was effective and the students acquired basic knowledge on zoonoses and ways to prevent transmission after participating in the school zoonotic diseases awareness program.